2021
DOI: 10.23922/jarc.2021-024
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Recurrence of External Rectal Prolapse after Laparoscopic Ventral Rectopexy

Abstract: Objectives: This study aimed to evaluate factors that contribute to the recurrence of external rectal prolapse (ERP) following laparoscopic ventral rectopexy (LVR). Methods: All patients who underwent LVR using synthetic meshes between 2011 and 2018 were prospectively included. A standard questionnaire including the Fecal Incontinence Severity Index (FISI) and Constipation Scoring System (CSS) was administered preoperatively and postoperatively. Defecography was performed 6 months postoperatively. Univariate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In our assessment for LVMR, although there were differences in symptom improvement compared to other studies, postoperative FI showed a significant improvement of 95.5% at the 4-year follow-up, whereas ODS demonstrated a significant improvement of 92.3%. These findings are consistent with another study [ 42 ]. The observed improvement in ODS symptoms after LVMR can be attributed to the autonomic nerve-sparing surgical technique [ 9 ].…”
Section: Discussionsupporting
confidence: 94%
“…In our assessment for LVMR, although there were differences in symptom improvement compared to other studies, postoperative FI showed a significant improvement of 95.5% at the 4-year follow-up, whereas ODS demonstrated a significant improvement of 92.3%. These findings are consistent with another study [ 42 ]. The observed improvement in ODS symptoms after LVMR can be attributed to the autonomic nerve-sparing surgical technique [ 9 ].…”
Section: Discussionsupporting
confidence: 94%
“…While, a recent study has reported a lower recurrence rate (4.3%, 2 out of 47 cases) for the modified Delorme's procedure, where the length of stripped rectal mucosa was maintained 3 to 4 times the length of the exteriorized prolapse [20], a comprehensive review article highlighted a lower recurrence rate for ERP after LVR when compared to Delorme's procedure (2% [15/680] versus 20% [154/ 770]) [19]. However, considering reports of increased recurrence risk in older patients post-LVR [21,22], and the observation that all recurrences (nine out of 132 patients) occurred within the initial 12 months post-surgery [14], a follow-up period of at least 12 months is recommended, even for nonagenarian patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most common technical cause of recurrence or repair failure is due to mesh detachment from the sacral promontory [11]. Other reported risk factors for recurrence after LVR include age >70, male sex, high BMI, and prolonged pudendal nerve terminal motor latency, none of which are related to the surgical technique [12,13]. With experienced laparoscopic surgeons doing precise dissection of the rectovaginal septum and adequate xation of the mesh to the lower rectum and the sacral promontory, we would not expect signi cant difference in outcomes with RVR and LVR.…”
Section: Discussionmentioning
confidence: 99%